2001
DOI: 10.1038/sj.jhh.1001131
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and its determinants among adults in high mountain villages of the Northern Areas of Pakistan

Abstract: We studied the prevalence and determinants of hypertension among adults in mountainous rural villages in the Ghizar district Northern Areas of Pakistan, an area that recently has undergone substantial economic development. We selected a stratified random sample of 4203 adults (age Ͼ18 years) from 16 villages in Punial Valley of Ghizar district where the number of study subjects from each village was proportionate to the size of the village. We obtained blood pressure (BP) records by taking the mean of the seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 17 publications
6
19
0
Order By: Relevance
“…Several studies have shown the significant association between hypertension and BMI. [14][15][16][17]20,21 Wasir HS et.al, Singh RB et.al and several other studies have found that lower physical activity was positively associated with hypertension and thus present study findings are comparable to them. 15,16,20,25,26 …”
Section: Risk Factors Of Hypertensionsupporting
confidence: 81%
See 1 more Smart Citation
“…Several studies have shown the significant association between hypertension and BMI. [14][15][16][17]20,21 Wasir HS et.al, Singh RB et.al and several other studies have found that lower physical activity was positively associated with hypertension and thus present study findings are comparable to them. 15,16,20,25,26 …”
Section: Risk Factors Of Hypertensionsupporting
confidence: 81%
“…16 Shah SMA et.al.in their study among adults of Pakistan found age to be independently associated with higher prevalence of hypertension. 17 Cappuccino FP et.al in their study in African population found the prevalence of hypertension increased with age. 18 Current study can be compared to other study from Nepal.…”
Section: Risk Factors Of Hypertensionmentioning
confidence: 99%
“…Similar to other studies, the risk of hypertension increased with age [7][8][9][10][11][12]. This progressive increase is linked with rising systolic BP, increasing with age to an average value close to 140 mmHg in the 7th decade [13].…”
Section: Discussionsupporting
confidence: 70%
“…24,25 The prevalence of hypertension in Bavi was low compared to national figures in developed countries such as the United States of America, Australia and the United Kingdom, as well as other developing countries such as Thailand, Indonesia and China. 4,[26][27][28] Comparing studies conducted in rural areas in developing countries, the hypertension prevalence found in this study was slightly lower than the one revealed in a rural community of India (17.3% among people aged 25-64 years) 29 but higher than the figures of 15% in a remote rural region of Pakistan 11 and of 10% in rural communities of Iran. 30 This study also revealed an unacceptably high percentage of hypertensives (83%) not being aware of their high blood pressure.…”
Section: Discussionmentioning
confidence: 65%
“…Blood pressure levels and hypertension have been proven to be inversely related to socioeconomic status in developed countries, [6][7][8] but in the developing world such correlations have not always been evident. [7][8][9][10][11][12] Vietnam, a developing country in Southeast Asia, is undergoing an early stage of health transition where the population is suffering from the 'double burden' of old communicable diseases and emerging noncommunicable diseases (NCDs). 13 According to hospital statistics, hypertension was the third contributor to the burden of death and the sixth contributor to the burden of disease in hospitals for the whole country in 2002.…”
Section: Introductionmentioning
confidence: 99%